Attitudes and achievement in statistics: a meta-analytic and functional near-infrared spectroscopy approach - Wagenaar, Emma Kate (Rhodes University, Faculty of Humanities, Department of Psychology)
Statistics anxiety describes the extensive worry and apprehension that students may experience when faced with statistics content as part of their university curriculums. Student's perfunctory disposition towards statistics has been indicated to negatively affect performance outcomes in statistics courses. Two meta-analyses were conducted to investigate the relationship between statistics anxiety and achievement in statistics. The first meta-analysis was inclusive of 22 studies investigating the relationship attitudes towards statistics and achievement, whilst the second meta-analysis focused on the relationship, primary amongst Psychology students. Student's attitudes towards statistics were measured using the Survey of Attitudes Towards Statistics (SATS), whilst achievement in statistics courses was quantified using different outcome measures. Finding from the meta-analysis were supplemented by cortical mapping of the neural correlates of statistical reasoning using functional near-infrared spectroscopy (fNIRS). Results from the meta-analysis indicated a small significant relationship between university students' Affect, r = 0.28, Value, r = 0.22 and Difficulty, r = 0.18, and subsequent achievement in statistics courses. A medium significant relationship between Cognitive Competence, r = 0.31, and achievement was also noted. Findings from the second meta-analysis, indicated a medium, significant relationship between Affect, r = 0.32, and Cognitive Competence, r = 0.35, and achievement. Moreover, a small significant relationship was found between Value, r = 0.24, and Difficulty, r = 0.23, in relation to achievement in statistics courses. Case study analysis of the neural correlates of statistics reasoning revealed varied signal quality findings of cortical mapping of the neural correlates of statistics in the dorsolateral prefrontal cortex (DLPFC). Moreover, seed-based correlation analysis indicated cortical activation of the dorsolateral prefrontal cortex paired with diverse prefrontal regions. Recommendations from the study include improvements to the fNIRS research design and the inclusion of larger samples to investigate the cortical mapping of the DLPFC in relation to statistics reasoning and statistics anxiety.
Keywords: Statistics-- Study and teaching; fNIRS; Dorsolateral prefrontal cortex; Learning, Psychology of; Academic achievement